Bulk viscosity of water in acoustic modal analysis and experiment - Kůrečka, Jan; Habán, Vladimír; Himr, Daniel (EDP Sciences, 2018)
Bulk viscosity is an important factor in the damping properties of fluid systems and exhibits frequency dependent behaviour. A comparison between modal analysis in ANSYS Acoustics, custom code and experimental data is presented in this paper. The measured system consists of closed ended water-filled steel pipes of different lengths. The influence of a pipe wall, flanges on both ends and longitudinal waves in the structural part were included in measurement evaluation. Therefore, the obtained values of sound speed and bulk viscosity are parameters of the fluid. A numerical simulation was carried out only using fluid volume in a range of bulk viscosity. Damping characteristics in this range were compared to measured values. The results show a significant influence of sound speed and subsequently, the use of sound speed value regressed from experimental data yields a better fit between the measurement and the computation.

Bulk viscosity is an important factor in the damping properties of fluid systems and exhibits frequency dependent behaviour. A comparison between modal analysis in ANSYS Acoustics, custom code and experimental data is presented in this paper. The measured system consists of closed ended water-filled steel pipes of different lengths. The influence of a pipe wall, flanges on both ends and longitudinal waves in the structural part were included in measurement evaluation. Therefore, the obtained values of sound speed and bulk viscosity are parameters of the fluid. A numerical simulation was carried out only using fluid volume in a range of bulk viscosity. Damping characteristics in this range were compared to measured values. The results show a significant influence of sound speed and subsequently, the use of sound speed value regressed from experimental data yields a better fit between the measurement and the computation.
Bulk viscosity of water in acoustic modal analysis and experiment
Keywords: bulk viscosity; fluid acoustics; bulk viscosity; fluid acoustics